Advances in Understanding Defense Mechanisms in Persea americana Against Phytophthora cinnamomi - van den Berg, Noëlani; Swart, Velushka; Backer, Robert; Fick, Alicia; Wienk, Raven; Engelbrecht, Juanita; Prabhu, S. Ashok (Frontiers in Plant Science, 2021)
Avocado (Persea americana) is an economically important fruit crop world-wide, the production of which is challenged by notable root pathogens such as Phytophthora cinnamomi and Rosellinia necatrix. Arguably the most prevalent, P. cinnamomi, is a hemi-biotrophic oomycete which causes Phytophthora root rot, leading to reduced yields and eventual tree death. Despite its’ importance, the development of molecular tools and resources have been historically limited, prohibiting significant progress toward understanding this important host-pathogen interaction. The development of a nested qPCR assay capable of quantifying P. cinnamomi during avocado infection has enabled us to distinguish avocado rootstocks as either resistant or tolerant-an important distinction when unraveling the defense response. This review will provide an overview of our current knowledge on the molecular defense pathways utilized in resistant avocado rootstock against P. cinnamomi. Notably, avocado demonstrates a biphasic phytohormone profile in response to P. cinnamomi infection which allows for the timely expression of pathogenesis-related genes via the NPR1 defense response pathway. Cell wall modification via callose deposition and lignification have also been implicated in the resistant response. Recent advances such as composite plant transformation, SNP analyses as well as genomics and transcriptomics will complement existing molecular, histological, and biochemical assay studies and further elucidate avocado defense mechanisms.